2021
DOI: 10.29333/iejme/11090
|View full text |Cite
|
Sign up to set email alerts
|

Dismantling the ‘All-Boys Club’ A Narrative of Contradictions Women Experience in PhD Mathematics Programs: A Freirean Approach

Abstract: Gender issues in mathematics education received fairly attention several decades ago, mainly because women and men performed differently, with men usually outperforming women. The research on such phenomena originated a series of studies on the so-called 'achievement-gap.' After many years of research on the achievement gap, such a gap has shown to have disappeared. However, recent studies have shown that there are fewer women who choose STEM-related fields than male peers. Suppose women are not choosing mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Despite years of research on the inequity in STEM education and careers, certain groups continue to be underrepresented (Ataide Pinheiro, 2021;National Center for Science and Engineering Statistics, 2021;Neto & Ataide Pinheiro, 2021). Students are often assigned to these groups using single identity qualifiers (e.g., gender, race, low socioeconomic status [SES]).…”
Section: Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite years of research on the inequity in STEM education and careers, certain groups continue to be underrepresented (Ataide Pinheiro, 2021;National Center for Science and Engineering Statistics, 2021;Neto & Ataide Pinheiro, 2021). Students are often assigned to these groups using single identity qualifiers (e.g., gender, race, low socioeconomic status [SES]).…”
Section: Identitymentioning
confidence: 99%
“…In addition, the field has also begun to recognize gender as a social construct rather than as biological sex (Butler, 1990(Butler, , 1999Damarin & Erchick, 2010;Esmonde, 2011;Rubel, 2016). This is important because, traditionally, gender research has focused solely on women (see Ataide Pinheiro, 2021). However, scholars have contended that gender research should also focus on men, the differences found within male/female gaps (Buck et al, 2020), and be expanded to include LGBTQ+ individuals (Ataide Pinheiro, 2022;Scantlebury & Baker, 2007).…”
Section: Gender and Sexuality In Stem Researchmentioning
confidence: 99%